The Breast Cancer Weight Loss trial (Alliance A011401): A description and evidence for the lifestyle intervention. Issue 1 (21st December 2021) - Delahanty, Linda M.; Wadden, Thomas A.; Goodwin, Pamela J.; Alfano, Catherine M.; Thomson, Cynthia A.; Irwin, Melinda L.; Neuhouser, Marian L.; Crane, Tracy E.; Frank, Elizabeth; Spears, Patricia A.; Gillis, Bonnie P.; Hershman, Dawn L.; et al.
Abstract: The Breast Cancer Weight Loss (BWEL) trial is a randomized controlled trial designed to determine whether weight loss after a breast cancer diagnosis can reduce the risk of cancer recurrence in women with overweight or obesity. The BWEL trial will compare the efficacy of a telephone‐based weight‐loss intervention plus health education materials versus health education materials alone on invasive disease‐free survival in 3, 181 women with stage II or III breast cancer and BMI > 27 kg/m 2 . This report provides a detailed description of the goals and methods of the lifestyle intervention and the evidence supporting the intervention used in the BWEL trial. The intervention's primary goal for participants is to achieve and maintain a weight loss ≥ 10% of baseline weight through increased physical activity and caloric restriction. The evidence supporting the diet, physical activity, and behavioral components of this telephone‐based weight‐loss intervention, as well as strategies to promote participant engagement and retention, is described. The intervention is provided through 42 sessions delivered by trained health coaches over a 2‐year period. If the BWEL lifestyle intervention is successful in improving cancer outcomes, then weight loss will be incorporated into the care of thousands of breast cancer patients.